Study of shear strength on soil using static standard penetration test (SSPT) / Syazana Syahirah Jamaluddin - Jamaluddin, Syazana Syahirah (2015)
In this study, a series of laboratory modeling testing is presented to study the shear strength of the soil using static load test performed in a prototype Static Standard Penetration Test (SSPT) tank. Static Standard Penetration Test (SSPT) is a new combination method of Standard Penetration Test (SPT) and Cone Penetration Test (CPT) to obtain an undisturbed sample. The difference is that SPT is driven by blows using the dynamic force to penetrate the sampler into the soil. SSPT is applying the measured force to the rod where the sampler is pushed into the soil continuously using static force at a uniform rate of penetration to collect sample. The transducer and the load cell will be connected to the computer to record every second of time, depth of penetration of the sampler and measured force for the sampler to penetrate into the soil. Subsequently, an analytical formula for determining the shear strength of soil has been developed from the result of unconfined compression test (UCT). It is shown that the formula to determine the shear strength of the soil can be reasonably used.